Performance improvement of 4G OFDM systems using CTSTC techniques - Padmaja, C; L. Malleswari, B (International Journal of Engineering and Technology, 2018)
The concatenation of channel coding and diversity schemes are essential in the 4G communication systems to improve the reliable data rate transmission. To address Bit Error Rate performance enhancement, the paper presents the coding gain and diversity gain benefits using the proposed CTSTC scheme by adding modified Turbo features and Space Time encoding features. Simulation results of are provided using MATLAB and compared the results with convolutional coded Space Time Coding technique.Â Â